Environmental Democracy at the Global Level : Rights and Duties for a New Citizenship - Parola, Giulia (De Gruyter Open, 2013)
Giulia Parola's Environmental Democracy at the Global Level: Rights and Duties for a New Citizenship can be seen as a manifesto that is both traditional and revolutionary at the same time. It calls for the construction of a new civilisation centred on the environment, while drawing on the traditional notions of democratic government. It adopts an approach that is focused on the power of individuals rather than governments, as ways to protect and improve the environment. It proposes that environmental rights and ecological duties are self-evident and inalienable, and should be treated as the cornerstones of a new democracy. Parola's book is a thought provoking and intriguing work that will be of interest to scholars of environmental studies as well as to legal practitioners and non-specialists. Giulia Parola has studied Environmental Law at the University of Torino, at the University of René Descartes in Paris, (where she obtained PhD in Public Law) and at the University of Iceland (LLM in Natural Resources Law and International Environmental Law). In 2011, she was appointed by the University of Laval (Canada, Quebec) as a researcher and a lecturer in Environmental Law.
Keywords: Democracy -- Environmental aspects.; Environmental law -- European Union countries.; Environmental policy -- Citizen participation.; LAW / Civil Law.; Democracy.; Environmental law.; European Union countries.; Electronic books.